Implementation of Field Study Courses in the Pre-Service Teacher Education Program in Selected Higher Education Institutions in Caraga - Patan, Juvy P. (JPAIR Multidisciplinary Research, 2010)
This study aimed to assess the extent of implementation of Field Study Courses in the Pre-Service Teacher Education Program in the Selected Higher Education Institutions in Caraga. Specifically, this study was conducted in the Teacher Education Institutions of Fr. Saturnino Urios University, Saint Paul University System, Surigao State College of Technology, and Surigao del Sur Polytechnic State College Academic Year 2009-2010. The respondents of this study were the HEI's deans and supervising deans; DepEd principals and field study resource teachers; and field study students in the selected HEI's in Caraga. The implementation of curriculum through course syllabus, requirements, deployment and assessment should be properly observed. There is a need to increase the honoraria of resource teachers to compensate their efforts in sharing inputs to the students of Field Study courses. Regular orientation and re-orientation should be done among the students of Field Study courses on work and values enhancement to improve students' attitudes and behavior for better performance.
Keywords: pre-service; teacher; higher education